Tinjauan Aspek Keamanan dan Kerahasiaan Rekam Medis di Ruang Penyimpanan Rumah Sakit Bina Kasih Pekanbaru Tahun 2024 - Nurjanah, Ana; Trisna, Wen Via (Lembaga Penerbitan Universitas Esa Unggul, 2024)
AbstractThe medical record storage room must comply with applicable standards to ensure the security and confidentiality of medical records. At Bina Kasih Hospital, there are still issues with security, such as staff eating and drinking in the storage room, inadequate lighting, and dusty medical records. This study aims to assess the security and confidentiality of medical records in the storage room of Bina Kasih Hospital in Pekanbaru, Riau. The method used is a qualitative approach with a descriptive design. Three informants participated in this study: one head of medical records and two medical record staff. Data were collected through interviews and observation techniques. The study's results showed that, from the physical aspect, the humidity in the storage room was around 50%, and the temperature was around 25˚C, measured using a thermohygrometer. However, the lighting in the room was insufficient due to overcrowded racks, preventing light from spreading correctly. The light intensity was measured at 39 lux near the storage racks and 65 lux near the medical record staff's desk. From the chemical aspect, staff were still eating and drinking in the room. From the biological aspect, some medical records were damaged by termite bites. Regarding the confidentiality of medical records, the storage room door was secured with a fingerprint code that only medical record staff knew, preventing unauthorized personnel from entering without permission. The study concluded that the lighting in the room remains inadequate, staff still eat and drink in the room, and termites damaged some medical records. However, the confidentiality of medical records is well-maintained. It is recommended to add more lighting to the storage room, install